2000
DOI: 10.1046/j.1523-1755.2000.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal platelet cytoskeletal assembly in hemodialyzed patients results in deficient tyrosine phosphorylation signaling

Abstract: Our present data support the concept that repeated platelet stress during hemodialysis has a deleterious effect on the organization of platelet cytoskeleton, which seems to impair the translocation of signal transduction proteins within platelets compromising the platelet function in uremia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
0
14
0
3
Order By: Relevance
“…5,7 As these phenomena occur three times a week, month after months, it has been suggested that PLTs from chronic HD subjects are depleted and, in combination with the uremic environment, persistently deficient. 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…5,7 As these phenomena occur three times a week, month after months, it has been suggested that PLTs from chronic HD subjects are depleted and, in combination with the uremic environment, persistently deficient. 8,9 …”
Section: Discussionmentioning
confidence: 99%
“…Além disso, observamos que uma proporção significativamente maior de pacientes que não apresentavam defeito trombofílico recebeu tratamento com hemodiálise antes do transplante. O tratamento com hemodiálise é acompanhado por alterações estruturais e funcionais específicas nas plaquetas, 32 podendo, também, ter contribuído para equiparar a prevalência das complicações trombóticas dos pacientes sem defeito trombofílico com a observada entre os pacientes que o apresentavam.…”
Section: Discussionunclassified
“…Отримання білкових фракцій тромбоци-тів, що містять різні пули актину, проводили руйнуванням клітин за допомогою Triton X-100-вмісного буфера та наступного дифе-ренціального центрифугування [7]. Відразу після проведення агрегометрії до суспензії тромбоцитів вносили рівний об'єм лізуючо-го буфера такого складу: 100 ммоль/л тріс-HCl (рН 7,4), 2% Triton X-100, 10 ммоль/л етиленглікольтетраоцтової кислоти, 2 мкг/ мл лейпептину, 100 ммоль/л бензамідину, 2 ммоль/л фенілметилсульфонілфлуориду, 2 ммоль/л ванадату натрію.…”
Section: методикаunclassified
“…Як припускалося раніше [7], відсутність атиа-грегативної активності Glu-плазміногену може пояснюватися його більш закритою у порівнянні з Lys-формою конформацією, внаслідок чого центри міжмолекулярного розпізнавання, що знаходяться у крингло-вих доменах, опиняються недоступними для взаємодії зі специфічними лігандами. Незважаючи на те, що плазміноген цирку-лює у плазмі тільки у вигляді Glu-форми, фізіологічне значення Lys-плазміногену як регулятора активності клітин не можна ви-ключати [8].…”
Section: результати та їх обговоренняunclassified